Enhancement of photocatalytic and antimicrobial properties of SHMP-capped with Ni and Gd-doped zinc oxide nanoparticles - Kumar Mageswari; Thirugnanam Bavani; Jagannathan Madhavan; Peethambaram Prabukanthan (Hybrid Advances)
This work describes the development of Gd-doped zinc oxide nanoparticles with SHMP (sodium hexametaphosphate) capped Ni (3 wt%) using a microwave-aided synthesis method.The Gd content was varied at 1, 2, 3, 4, and 5 wt%. Several advanced analytical methods were used to analyze the metal-doped zinc oxide nanoparticles. The results showed that incorporating SHMP-capped with Ni and Gd mostly affects the structural and optical properties of zinc oxide nanoparticles. Under visible light, the optimized SHMP-capped Ni and Gd (4 wt%) doped zinc oxide nanoparticles showed better photocatalytic degradation towards methylene blue (MB). The addition of SHMP-capped with Ni and Gd doped on zinc oxide nanoparticles was responsible for this improvement. Moreover, the antibacterial efficacy and outcomes of the bi-metal doped zinc oxide nanoparticles were assessed against E. Coli species. The synthesized SHMP-capped with Ni and Gd-doped zinc oxide nanoparticles are hence promising materials for two different uses.